2016
DOI: 10.1016/j.chemosphere.2016.04.096
|View full text |Cite
|
Sign up to set email alerts
|

Using isotopic dilution to assess chemical extraction of labile Ni, Cu, Zn, Cd and Pb in soils

Abstract: Highlights: Stable isotope dilution can inform underlying mechanisms during chemical extraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…The element lability in contaminated soils and mining wastes is a more relevant indicator for environmental risk than total concentrations (Hamon et al, 2008). The median %E values of Cu, Zn, and Cd for the soil samples were 10-20% lower than the median of previously reported values for Cu (17%, n = 87), Zn (23%, n = 101), and Cd (30%, n = 105) obtained using the same protocol (Buekers et al, 2007;Garforth et al, 2016;Hamon et al, 2008;Marzouk et al, 2013b). Labile fractions of Ni and Pb were very comparable with the same set of reported values.…”
Section: Total and Labile Metal Concentrationssupporting
confidence: 79%
See 3 more Smart Citations
“…The element lability in contaminated soils and mining wastes is a more relevant indicator for environmental risk than total concentrations (Hamon et al, 2008). The median %E values of Cu, Zn, and Cd for the soil samples were 10-20% lower than the median of previously reported values for Cu (17%, n = 87), Zn (23%, n = 101), and Cd (30%, n = 105) obtained using the same protocol (Buekers et al, 2007;Garforth et al, 2016;Hamon et al, 2008;Marzouk et al, 2013b). Labile fractions of Ni and Pb were very comparable with the same set of reported values.…”
Section: Total and Labile Metal Concentrationssupporting
confidence: 79%
“…A main reason for the discrepancies is the type of sampled analyzed, as T A B L E 3 Significant (p < .01) linear regression parameters (m 1 to m 4, Equation 4) from stepwise multivariate analysis of labile fractions (%E) of Ni, Cu, Zn, Cd, Pb, and As as a function of soil chemical properties and contamination source attributes Mao et al (2017). in the case of Buekers et al (2007), where high fractions of labile Cu and Cd correspond to control-uncontaminated soils. When field-contaminated soils are analyzed (as in Garforth et al (2016) and Marzouk et al (2013b), the discrepancies are more related to soil chemical properties (mainly to lower pH values and oxalate-extractable Fe contents compared with the values of the present work). Median As %E values are in good agreement with the median of reported values in contaminated soils (8.2; n = 27) determined with similar protocols (De Brouwere et al, 2004).…”
Section: Total and Labile Metal Concentrationscontrasting
confidence: 55%
See 2 more Smart Citations
“…Some authors have reported that Pb fixation by soil organic matter is an important factor associated with accumulation of Pb in soils with higher organic matter content (Li et al 1996;Garforth et al 2016). Soils that have high organic matter content may fix or immobilize Pb in the upper horizon, reducing its bioavailability and thus reducing its toxicity to organisms.…”
Section: Influence Of Soil Properties On Pb Toxicitymentioning
confidence: 99%